منطقة التجارة الحرة العربية الكبرى درس الماضي وآفاق المستقبل - العمري, حسين (Université de M'sila, 2009)
The aim of this paper is to follow up the outcome of the Arab free trade zone on the extent of the impact resulting from the perspective of the Arab economic integration, and especially after the World Trade Organization, and the acceleration of the various States for the establishment of economic blocs. It also aims to assess the importance of the Arab free trade zone in the process of Arab economic integration, and to assess the impact of the Arab free trade zone in the inter-Arab trade.